The red ribbon in francophone Africa.A Rhetorical analysis of social marketing against Aids. - (:unkn) unknown (My University, 2012)
One of the greatest challenges of the XXI Century in francophone African countries will be the political, economic and social combat against Aids. Facing a catastrophic situation, francophone African States have introduced large programs to fight. Our article will focus on strategies of persuasion adopted by both international and national organizations in order to detach the specialties of their rhetorical actions. This contribution brings a semiodiscursive reflection on the analysis of some posters. The purpose of this article is to show how the social marketing in favor of condom intends to influence people’s minds.
Keywords: African Research